Digital Parenting among Students with Intellectual Disabilities: Challenges & Strategies - Kushwaha, Ravindra Kumar; Yadav, Mukesh Kumar; Ahmad, Sarfaraz (International Journal of Religion Education and Law, 2024)
The rapid advancement of digital technology has significantly transformed various aspects of society, including education. In recent years, the integration of digital tools in educational settings has gained momentum, presenting both opportunities and challenges for students with intellectual disabilities. Digital parenting, which involves guiding and supporting children's use of digital devices and online resources, plays a crucial role in ensuring a safe and productive digital experience. This study aims to explore the challenges and strategies related to digital parenting among students with intellectual disabilities.